Towards a gender responsive occupational safety and health policy: An Exploratory study of gender needs and gender sensitive indicators. - Abd Talib, Lilis Surienty (Universiti Sains Malaysia, 2015)
Although Malaysia has made considerable advancement in gender equality in workplace, little is known of how gender equality is assessed and addressed in specific area of employment such as the health and safety of workers at work. This research aims at developing insight on a gender responsive occupational safety and health policy in Malaysia.